KOMUNIKASI ORANG TUA DAN ANAK DALAM MENONTON SINETRON TELEVISI DI KELURAHAN FAKFAK SELATAN KABUPATEN FAKFAK - Jecklin Titaley; Sudirman Karnay (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Hasanuddin, 2016)
The research objectives are (1) to know Communication of Parents and Children in watching the television series in South Fakfak district, Fakfak Region.. (2) To get the factors which have influenced Communication of Parents and Children In watching the television series in South Fakfak district, Fakfak Region..The research is conducted in South Fakfak District, Fakfak Region. People who are taken with purpose sampling such as chosen according consideration that they are eligible to respond the researcher’s questions. The primer resource is gotten through observation and interview with all informants deeply. While, the seconder resource is gotten through library study as like journals, and others which relate to the research problems.The first result of research points is Communication of Parents and Children In watching the television series in South Fakfak district, Fakfak Region is looked goodly. Parents are realized, concerning the important comprehension to the children. Literacy level (melek) has the main role into the television series in South Fakfak district, Fakfak Region. series program comprehension level in south Fakfak district, Fakfak region. Throughout parents have being openness, empathy, supporting, positiveness, and sameness at the children to motivate them to grasp more understood what their watched, beside that children find the explanation from parents by series scenes which they are seen, as good as to imitate and as unable as to consume it. The next result of research points is to give comprehension, regarding the cinema scenes which is seen by children are to need communication between individuals have effective and balance continuously. It means children understand what their parents’ want and so do they, in order that the good related and matched communication for what as parents’ hope. Media melek which parents have that can be accompanying kids to know the value contents in the series program, so that the kids get worthy things and do not to follow it Tujuan penelitian ini adalah : ( 1 ) Untuk mengetahui komunikasi Orang tua dan Anak Dalam Menonton Sinetron Televise Di Kelurahan Fakfak Selatan Kabupaten Fakfak; (2) untuk mengetahui faktor-faktor yang memengaruhi komunikasi Orang tua dan Anak Dalam Menonton Sinetron Televise Di Kelurahan Fakfak Selatan Kabupaten Fakfak Penelitian ini dilaksanakan di Kabupaten Fakfak, Kelurahan Fakfak Selatan. Orang-orang yang ditentukan secara purposive sampling yaitu dipilih berdasarkan pertimbangan tertentu bahwa mereka dianggap berkompeten untuk menjawab pertanyaan peneliti. Data primer diperoleh melalui observasi dan wawancara mendalam dengan para informan. Sedangkan data sekunder diperoleh melalui studi pustaka berupa buku-buku jurnal dan sebagainya yang berkaitan dengan masalah yang diteliti.Hasil penelitian menunjukkan komunikasi orang tua dan anak dalam menonton sinetron televise di kelurahan fakfak selatan kabupaten fakfak terlihat sangat baik, orang tua tentu sadar akan pentingnya memberikan pemahaman terhadap anak. Tingkat literasi ( melek ) media memiliki peran penting dalam komunikasi orang tua dan anak. Melalui Ornag tua Dengan adanya keterbukaan, empati, dukungan, rasa positif dan kesamaan terhadap anak dapat mendorong anak untuk dapat lebih memahami apa yang tonton olehnya selain itu anak juga akan mendapatkan Penjelasan dari orang tua terhadap tayangan sinetron yang di tonton, layak ditiru dan layak untuk tidak di tiru. Untuk dapat memberikan pemahaman tentang tayangan sinetron yang di tonton pada anak di butuhkan Komunikasi Antar Pribadi yang efektif dan berlangsung seimbang. Artinya anak mengerti apa yang diinginkan oleh orang tua begitu pun sebaliknya agar terjalin komunikasi yang baik dan sesuai dengan apa yang orang tua harapkan. Melek media yang orang tua punya dapat mendampingi anak dalam mengetahui nilai-nilai yang terkandung dari program sinetron yang di tonton, agar anak dapat mengetahui yang pantas dan tidak untuk diikuti.